Impact of Government Spending In Social Sectors on Economic Growth: A Case Study of West African Economic and Monetary Union Countries (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to investigate the short-run and long-run effects of government’s social expenditure proxies, namely education, and health spending on economic growth during the period 1985 - 2019 in West African Economic and Monetary Union. Using Auto Regressive Distributed Lag model (ARDL) based on panel data, the results of the study reveal that in short-run, government spending in social sectors has no significant impact on economic growth but in long-run the effects of education and health expenditures on the economic growth are significantly positive.